Infectious complications in patients with crush syndrome following the Wenchuan earthquake - ZHANG Hui; ZENG Jian-wei; WANG Guang-lin; TU Chong-qi; HUANG Fu-guo; PEI Fu-xing (Chinese Journal of Traumatology, 2013)
【Abstract】 Objective: To analyze the results of clini-cal and bacteriological examinations in patients with crush syndrome who suffered infectious complications after an earthquake in Sichuan, China. Methods: A total of 313 bacteriological samples among 147 patients with crush syndrome were collected. Infectious complications, results of microbiological examinations, po-tential risk factors of infection and mortality were analyzed statistically. Results: In the obtained database, 112 out of the 147 (75.7%) patients had infectious complications, in which, wound infection, pulmonary infection, and sepsis were most common. The time under the rubble and the time from injury to treatment were related to the occurrence of wound infec-tion (P=0.013, odds ratio 2.25; P=0.017, odds ratio 2.31). Sep-sis and wound infection were more common in patients who underwent fasciotomy or amputation than in those who did not (P=0.001). Conclusion: Quick rescue and injury treatment can decrease the infection risk in crush syndrome patients. It is better to obtain microorganic proofs before applying antibiotics, and bacteriological and drug sensitivity data should be taken into account, especially considering that most of these infections are hospital-acquired and drug resistance. Emphasizing the accuracy and efficiency of wound management in emergency situations, cautiously assessing the indications for fasciotomy to avoid open wounds from unnecessary osteofascial compartment de-compression incisions may decrease the incidence of in-fection and ameliorate the prognosis. Key words: Earthquakes; Crush syndrome; Infection; Microbial sensitivity tests